Lebanese pharmacy students respond to the Syrian refugees’ health needs as part of their curiculum - El Khoury, G. (2017)
The World Health Organization (WHO) has deliberately emphasized the role of pharmacists in global health. Academic institutions are encouraged to train its graduates to recognize and adequately address the social determinants of health as part of pharmacy professional education. Lebanon, a developing country of the Eastern Mediterranean region, is deeply affected by the Syrian crisis. As part of their ambulatory care rotation, pharmacy students responded to Syrian refugees’ needs.